DEVELOPING ADAPTIVE CAPACITY IN EDUCATIONAL LEADERSHIP TO NAVIGATE DIGITAL DISRUPTION AND GLOBALIZATION DYNAMICS - Asnawi Malik; Muntaha Mahfud; Miftahudin; Maulana Yusuf; Jamiu Temitope Sulaimon (PT. Cadas Insan Madani, 2026)
This article explores the development of adaptive capacity in educational leadership as a strategic response to the accelerating forces of digital disruption and globalization. In an era characterized by rapid technological advancement, shifting knowledge paradigms, and increasing global interconnectivity, educational leaders are required to move beyond traditional administrative roles toward more dynamic, flexible, and responsive leadership practices. The study emphasizes the importance of adaptive leadership competencies, including digital literacy, strategic foresight, collaborative decision-making, and innovation-driven management in educational institutions. Using a conceptual approach based on literature review, this paper synthesizes key theories of educational leadership, digital transformation, and globalization to construct an integrated framework for adaptive leadership capacity. The findings suggest that effective educational leadership in the contemporary era depends on the ability to continuously learn, reconfigure institutional practices, and foster a culture of innovation and resilience within educational organizations. Furthermore, the article highlights that globalization intensifies the complexity of educational governance by introducing cross-cultural dynamics, policy shifts, and competitive knowledge economies. In response, adaptive educational leaders must act as change agents who bridge local educational values with global standards and technological advancements. The study concludes that strengthening adaptive capacity is essential for ensuring the sustainability and relevance of education systems in the digital-global era.